An Extensive Evaluation of Brand Image with Moderating Effect of Brand Engagement to Determine Brand Loyalty and Consumers’ Purchase Intention: A Study of Famous Female Apparel Brands in Pakistan - Sandhu, Moeed Ahmad; Shabbir, Sadaf (Pakistan Journal of Humanities and Social Sciences, 2023)
This study extensively evaluated brand image and main purpose was to find out in what way Brand Engagement will moderate the influence of Brand Image on Brand Loyalty to determine customers’ purchase intention. Current research utilized the survey method for data collection. To study the relationships between variables, the selected industry was famous female apparel brands of Pakistan, in different cities such as Lahore, Islamabad, Sialkot and Multan. The current research used questionnaire as the research instrument to interact with the sampling population. Only females were targeted to get data. Non probability sampling techniques was utilized in the study that included convenience and snowball sampling. Sample size was 300. Current research showed that brand image possesses substantial positive effect on brand loyalty and all antecedents of brand image were positively affecting the brand image. Moreover, brand loyalty has also been established to have significant positive impact on purchase intention. Brand engagement showed insignificant negative result as a moderator between brand image and brand loyalty showing that customers are not emotionally committed to the brand of their choice instead they are just becoming loyal due to other reasons. The evaluation of Brand Image has been done by incorporating many unique antecedents and the relationship of these antecedents was checked with brand image to imply better appreciation of brand image. Furthermore moderating effect of brand engagement among brand image and brand loyalty was unknown in past researches. The contribution of this research is theoretical, practical as well as contextual since we have conducted this study on a matchless framework regarding the female apparel brands in Pakistan.